1982
DOI: 10.1136/vr.111.8.155
|View full text |Cite
|
Sign up to set email alerts
|

Survey of lameness in British dairy cattle

Abstract: During 1977 a survey was undertaken by practising veterinary surgeons of the incidence of different lesions causing lameness in dairy cattle. Forty-eight veterinary practices participated and they treated 7526 cases of lameness in 1821 herds. The average incidence of lameness among all cows was 5.5 per cent and the annual incidence among practices ranged from 1.8 to 11.8 per cent. Most lesions (88.3 per cent) occurred in the feet; the commonest were foul of the foot (16.7 per cent), white line abscess (15.6 pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
41
3
4

Year Published

1988
1988
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(56 citation statements)
references
References 0 publications
8
41
3
4
Order By: Relevance
“…The high lesion rate in feet is probably caused partly by the direct contact of feet with environments which are often unsuitable, i.e. hard, stony, wet or contaminated with faeces, and partly by the recent emphasis on the conformation of legs rather than feet in selecting bulls and cows for breeding [7,25]. Continued improvements in housing and flooring are essential to reduce the impact of these management changes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The high lesion rate in feet is probably caused partly by the direct contact of feet with environments which are often unsuitable, i.e. hard, stony, wet or contaminated with faeces, and partly by the recent emphasis on the conformation of legs rather than feet in selecting bulls and cows for breeding [7,25]. Continued improvements in housing and flooring are essential to reduce the impact of these management changes.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of the hind feet of 4896 cows in France at the end of the winter housing period, Philpot et al (1990) reported 55% of animals affected [30]. Russell et al (1982) reported that HHE was responsible for 8% of all lesions causing lameness in a British survey [25]. Moisture may contribute to an infection and to the persistence of superficial wounds, as well as predisposing cows to horn erosion, underrun sole and white line disease [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The steers were slaughtered at a commercial abattoir. The hind digits were selected for investigation because of the preponderance of claw lesions in hind lateral claws (8),…”
Section: Subjectsmentioning
confidence: 99%
“…One study indicated tendon involvement in 21% of limb lesions. 20 Another study reported that muscle and/or tendon lesions accounted for 74% of upper limb injuries in the forelimb and 7.8% in the hind limb. 21 Tendon injuries causing loss of a production animal or a decreased level of production result in significant economic loss.…”
Section: Tendon Disordersmentioning
confidence: 99%